Islamic Studies on the Metabolism Process of Vitamins and Minerals in the Body - Dinanti, Sri Wahyu; Oktavia, Lola; Hasanah, Qomariah (Yayasan Darussalam Bengkulu, 2022)
Humans to maintain survival need food as the most basic thing. However, it remains to be considered whether these foods have optimal nutritional value. The food consumed by humans must contain various kinds of nutritional content that can support human life processes. how optimal public health can be increased with the implementation of hygienic and halal food, this fulfills the criteria of good food in Islamic and health studies. This study uses a literature review method in which the researcher conducts a series of studies involving various kinds of information from the literature such as books, encyclopedias, documents, and so on. The data is described and analyzed by understanding and explaining it. with the aim of finding various kinds of theories and ideas which can then be formulated results in accordance with research objectives. Islam and health basically have the same goal for the good of humanity. Therefore, in consuming food there are several conditions that must be met and really paid attention to so that humans avoid various types of diseases that originate from food. The study of Islam in the Al-Quran is found in QS.AlBaqarah, 2:168 Halal food and thoyyib means food and drink that are permissible for consumption according to Islam, according to the type of food and how to obtain it. Halal in the understanding of fuqaha is lawful in terms of substance and process. It is also called thoyyib if the food is safe, good, and does not cause any problems if consumed, both short and long term and can provide benefits to the body.